Transistor Effect in the Cochlear Amplifier - KIEŁCZYŃSKI, Piotr; SZALEWSKI, Marek (Archives of Acoustics, 2014)
The paper presents a new electromechanical amplifying device i.e., an electromechanical biological transistor. This device is located in the outer hair cell (OHC), and constitutes a part of the Cochlear amplifier. The physical principle of operation of this new amplifying device is based on the phenomenon of forward mechanoelectrical transduction that occurs in the OHC’s stereocilia. Operation of this device is similar to that of classical electronic Field Effect Transistor (FET). In the considered electromechanical transistor the input signal is a mechanical (acoustic) signal. Whereas the output signal is an electric signal. It has been shown that the proposed electromechanical transistor can play a role of the active electromechanical controlled element that has the ability to amplify the power of input AC signals. The power required to amplify the input signals is extracted from a battery of DC voltage. In the considered electromechanical transistor, that operates in the amplifier circuit, mechanical input signal controls the flow of electric energy in the output circuit, from a battery of DC voltage to the load resistance. Small signal equivalent electrical circuit of the electromechanical transistor is developed. Numerical values of the electrical parameters of the equivalent circuit were evaluated. The range, which covers the levels of input signals (force and velocity) and output signals (voltage, current) was determined. The obtained data are consistent with physiological data. Exemplary numerical values of currents, voltages, forces, vibrational velocities and power gain (for the assumed input power levels below 1 picowatt (〖10〗^(-12) W), were given. This new electromechanical active device (transistor) can be responsible for power amplification in the cochlear amplifier in the inner ear.